Kesamaan Gender Pada Literasi Matematis Siswa: Implikasi Bagi Kesetaraan Gender Di Bidang STEM - Fointuna, Daniel Williams (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2025)
An adequate mathematical literacy allows individuals to comprehend core concepts in STEM fields, such as complex problem solving, analytical thinking, and methodical approach to challenges. Indonesian students’ mathematical literacy was still categorized in the low group according to PISA survey. In some countries, boys still outperformed girls which, in the long run, can lead to woman underrepresentation in STEM fields. Using secondary data collected during 2018/2019 academic year in Kupang, this research focused on examining public middle school students’ overall mathematical literacy based on gender as well as their performance in the process and content areas. The technique used to select 377 participants was two-stage cluster randomized sampling. Although there were only two categories of gender, the data were analyzed using One-Way ANOVAs to open possibilities for future research to analyze more than two groups. After the normality and homogeinity of variance had been confirmed, the data was then analyzed to examine gender patterns. The results revealed gender similarities in the overall as well as in the content and process domain of public middle school students’ mathematical literacy in Kupang. The results endorsed gender equality in mathematical literacy and contributed to career aspirations and decreasing gender prejudice in STEM education.